The Role of Vegetable Production as a Key Factor in Enhancing Cambodian Agriculture: A Systematic Review - Tan Mengly; Mardy Serey (Jurnal Semesta Ilmu Manajemen dan Ekonomi, 2024)
This systematic review examines the contribution of growing vegetables to effectively strengthen the Cambodian agriculture sector by enhancing food security and uplifting rural communities while promoting economic growth. This study sheds light on how cultivating vegetables impacts nutrition and income in areas by improving food availability and reducing poverty levels. Furthermore, it delves into aspects influencing vegetable cultivation in Cambodia, such as weather conditions, solid quality, input supply access, access to markets, and governmental regulations. The suggested measures include boosting funding for research efforts, improving infrastructure facilities, encouraging the processing of value-added products, supporting farmer groups, and embracing farming practices in Cambodia to develop a robust and thriving agricultural industry that ensures food security, fosters rural advancement, and drives economic progress.